INOVASI MANAJEMEN KURIKULUM DALAM MENGEMBANGKAN KREATIFITAS SISWA DI SMP PONDOK PESANTREN MODEREN AR-RISALAH KOTA LUBUK LINGGAU - Irawan, Novi; Warlizasusi, Jumira; Nation, Aida Rahimi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the planning, implementation, evaluation, and implications of curriculum management innovation in developing students' creativity at Ar-Risalah Modern Islamic Boarding School Junior High School, Lubuk Linggau City. The study employed a qualitative approach using a case study design. Data were collected through observation, interviews, and documentation, and were analyzed using the techniques of data reduction, data display, and conclusion drawing. The findings indicate that curriculum management innovation was implemented through the integration of the national curriculum and the Islamic boarding school curriculum, the application of active and creative learning strategies, the development of both curricular and extracurricular programs, and continuous curriculum evaluation. These innovations had a positive impact on the development of students' creativity, as reflected in their improved creative thinking skills, increased confidence in expressing ideas, enhanced problem-solving abilities, and active participation in various academic and non-academic activities. The study concludes that curriculum management innovation, implemented in a planned, integrated, and sustainable manner, effectively supports the optimal development of students' creativity at Ar-Risalah Modern Islamic Boarding School Junior High School, Lubuk Linggau City.